Early-life adversity increases anxiety-like behavior and modifies synaptic protein expression in a region-specific manner - Hamdan, Jameel N.; Sierra-Fonseca, Jorge A.; Flores, Rodolfo J.; Saucedo, Sigifredo; Miranda-Arango, Manuel; O’Dell, Laura E.; Gosselink, Kristin L. (Frontiers in Behavioral Neuroscience, 2022)
Early-life adversity (ELA) can induce persistent neurological changes and increase the risk for developing affective or substance use disorders. Disruptions to the reward circuitry of the brain and pathways serving motivation and emotion have been implicated in the link between ELA and altered adult behavior. The molecular mechanisms that mediate the long-term effects of ELA, however, are not fully understood. We examined whether ELA in the form of neonatal maternal separation (MatSep) modifies behavior and synaptic protein expression in adults. We hypothesized that MatSep would affect dopaminergic and glutamatergic signaling and enhance sensitivity to methamphetamine (Meth) reward or increase anxiety. Male Wistar rats were subjected to MatSep for 180 min/d on postnatal days (PND) 2-14 and allowed to grow to adulthood (PND 60) with no further manipulation. The hippocampus (Hipp), medial prefrontal cortex (mPFC), nucleus accumbens (NAc), and caudate putamen (CPu) were isolated from one subgroup of animals and subjected to Western blot and protein quantitation for tyrosine hydroxylase (TH), α-synuclein (ALPHA), NMDA receptor (NMDAR), dopamine receptor-1 (D1) and -2 (D2), dopamine transporter (DAT), and postsynaptic density 95 (PSD95). Separate group of animals were tested for anxiety-like behavior and conditioned place preference (CPP) to Meth at 0.0, 0.1, and 1.0 mg/kg doses. MatSep rats displayed an increase in basal levels of anxiety-like behavior compared to control animals. MatSep rats also demonstrated CPP to Meth, but their responses did not differ significantly from controls at any drug dose. Increased NMDAR, D2, and ALPHA expression was observed in the NAc and CPu following MatSep; D2 and ALPHA levels were also elevated in the mPFC, along with DAT. MatSep rats had reduced D1 expression in the mPFC and Hipp, with the Hipp also showing a reduction in D2. Only the CPu showed elevated TH and decreased DAT expression levels. No significant changes were found in PSD95 expression in MatSep rats. In conclusion, ELA is associated with long-lasting and region-specific changes in synaptic protein expression that diminish dopamine neurotransmission and increase anxiety-like behavior in adults. These findings illustrate potential mechanisms through which ELA may increase vulnerability to stress-related illness.